2008
DOI: 10.1080/10401330701798113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Student Reflective e-Portfolio on Medical Student Advisors

Abstract: Advisors reported students' reflective responses to focused questions in an e-portfolio contribute valuable understanding about students' thinking and attitudes. Advisors are enthusiastic about the value of the e-portfolio for this purpose. We anticipate benefits will generalize when fully implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…These were evaluated by two authors. Ninety‐one articles were selected that met the inclusion criteria for the review: 28 position paper overviews, six reviews, one meta‐analysis, two surveys, 19 quasi‐experimental studies, 10 mixed‐methods studies and 25 qualitative studies …”
Section: Resultsmentioning
confidence: 99%
“…These were evaluated by two authors. Ninety‐one articles were selected that met the inclusion criteria for the review: 28 position paper overviews, six reviews, one meta‐analysis, two surveys, 19 quasi‐experimental studies, 10 mixed‐methods studies and 25 qualitative studies …”
Section: Resultsmentioning
confidence: 99%
“…Although e-portfolios are being used in the health professions, results have been mixed. For example, Anderson et al (2009) and Bashook et al (2008) have reported that the more portable and adaptable e-portfolios are assisting students to become more reflective critical thinkers and providing educators early accurate insight into student thinking and reflective ability. Whereas a number of studies have found that issues with the technology, students understanding of competence and the assessments aligned with e-portfolios significantly impact on the usefulness for student learning (Cordier et al, 2015;Ferns & Comfort, 2014;Green, Wyllie, & Jackson, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…E-portfolios have been used across a variety of professions, including health, as a way to store evidence supporting the development and demonstration of professional competence (Anderson, Gardner, Ramsbotham, & Tones, 2009;Bashook, Gelula, Joshi, & Sandlow, 2008;Gowozdek, Springfield, & Kerschbaum, 2013). Although e-portfolios are being used in the health professions, results have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that many medical schools use different formats with some degree of success. Examples of these formats include using focus groups to identify important parameters (1); allowing mentoring relationships to evolve through informal rather than assigned student–faculty contact (2); randomly matching groups of students to a faculty member who meets with a small group of students weekly (3); assigning an individual advisor to each student, with an attempt to match them using background information (4); dividing the student body into groups, each headed by a faculty member who directs a very structured program (57); establishing advisory colleges, with students equally distributed in them, and integrating this into wellness programs and personal development programs (8, 9); linking advisory functions with the responsibilities of following the advisee's academic progress and writing the first draft of the Dean's Letter (10); using an electronic journal to keep advisors up to date on their advisees’ progress (11); using alumni as career counselors for medical students (12); and assigning a faculty member to attend classes during the first and second years (13). There are advantages and disadvantages to each of these programs, but a single clear pathway to success has not emerged.…”
Section: Introductionmentioning
confidence: 99%